Diversity, recombination and misclassification in the family Geminiviridae: Insight from bioinformatics analysis - Moshood Olamide Lateef; Dauda Nathaniel; Bolaji Osundahunsi; Neil Arvin Bretana (PLoS ONE, 2026)
The family Geminiviridae comprises 15 genera and over 500 species of diverse plant-infecting viruses. Previous studies on this virus’s diversity primarily focused on the members’ selection without considering the entire genomic divergence. This study presents comprehensive comparative genomic analyses and a global distribution map using 17,718 complete genomes and 28,185 geminivirus-associated metadata records. Intergeneric pairwise identity among monopartite and Begomovirus DNA-A is ≥ 40%, while interspecies identity among Begomovirus DNA-B is ≥ 41%, corresponding to genetic variations of ≤60% and ≤59%, respectively. Begomovirus and Mastrevirus are the only genera detected across all continents, with Asia exhibiting the highest genus diversity (11 genera). However, in Africa, geminiviruses from six genera are more broadly distributed across individual countries. To our knowledge, this is the first geographical map constructed using all genera from the Geminiviridae family. Phylogenetic reconstructions of complete genomes, coat proteins, and replication-associated proteins (Rep) underscored distinct clustering patterns consistent with genus-level classification but revealed exceptions, including misclassified viral species and potential new taxa. Notably, French bean severe leaf curl viru s with accession KC699544 was reclassified from Capulavirus to Begomovirus with the proposed name Corchorus yellow vein mosaic virus. Additionally, two unclassified begomovirus-like viruses, named “begomovirus spathoglottis 1” and “2,” are proposed for reclassification within Maldovirus under the tentative names “maldovirus spathoglottis 1” and “2.” The Begomovirus Rep showed phylogenetic affinity with Rep from Maldovirus, Curtovirus, Turncurtovirus, and Topocuvirus, supporting potential evolutionary relationships among these genera. Recombination analyses confirmed high-frequency interspecies and intergeneric recombination events, predominantly involving Begomovirus , underscoring its pivotal role in geminivirus evolution. Furthermore, we hypothesized specific vector transmission: Opunvirus , Welwivirus , and Topilevirus are transmitted via treehopper species, whereas Citlodavirus and Eragrovirus are transmitted via leafhopper species. Accurate identification and classification of plant viruses and their transmission vectors are essential for developing effective surveillance and management strategies to safeguard global agriculture.